Spatial Analysis of Road Network in Ramadi City (Iraqi Journal of Civil Engineering, 2023)
One of the most significant aspects of developing any region is establishing a viable road network and determining the relationship between landscape use and road networks. Adequate connectivity and direction are essential for the proper construction of any network. However, the Al-Ramadi road network has received far less attention and appraisal. As a result, the purpose of this study was to evaluate the current road network link in Al-Ramadi city. In addition, the GIS application was used in this study to show the city's primary features. The Alpha index, Beta index, Gamma index, and Eta index were utilized to evaluate the road network in this research. The primary goal of this research is to evaluate how successful the road network is in containing current road traffic and to make recommendations for the future traffic management efficiency to accommodate increase. The findings show that immediate upgrades, such as the construction of new roadways, are essential.